Occurrence of lace bug Vatiga illudens and Vatiga manihotae (Hemiptera: Tingidae) in Mato Grosso do Sul, midwestern Brazil - Bellon,Patrícia P. (2012)
Nymphs and adults of the lace bug (Hemiptera: Tingidae) have been found in cassava crops (Manihot esculenta) in Mato Grosso do Sul State, Brazil. The insects were collected in the field and taken to the laboratory where they were identified based on some morphological traits of the species Vatiga manihotae (Drake) and V. illudens (Drake), which are first reported in the aforementioned state.